Phase I/II trial of combined kyphoplasty and intraoperative radiotherapy in spinal metastases - Bludau, Frederic; Welzel, Grit; Reis, Tina; Schneider, Frank; Sperk, Elena; Neumaier, Christian; Ehmann, Michael; Clausen, Sven; Obertacke, Udo; Wenz, Frederik; Giordano, Frank Anton (The spine journal, 2018)
Background Context. Spinal metastases occur in 30%-50% of patients with systemic cancer. The primary goals of palliation are pain control and prevention of local recurrence. Purpose. This study aimed to test the safety and efficacy of a combined modality approach consisting of kyphoplasty and intraoperative radiotherapy (Kypho-IORT). Study Design/Setting Kyphoplasty and intraoperative radiotherapy was a prospective, single-center phase I/II trial. Patients were enrolled in a classical 3+3 scheme within the initial phase I, where Kypho-IORT was applied using a needle-shaped 50 kV X-ray source at three radiation dose levels (8 Gy in 8-mm, 8 Gy in 11-mm, and 8 Gy in 13-mm depth). Thereafter, cohort expansion was performed as phase II of the trial. The trial is registered with clinicaltrials.gov, number NCT01280032. Patient Sample Patients aged 50 years and older with a Karnofsky Performance Status of at least 60% and with one to three painful vertebral metastases confined to the vertebral body were eligible to participate. Outcome Measures The primary end point was safety as per the occurrence of dose-limiting toxicities. The secondary end points were pain reduction, local progression-free survival (L-PFS), and overall survival (OS). Methods Pain was measured using the visual analog scale (VAS) and local control was assessed in serial computed tomography or magnetic resonance imaging scans. Results None of the nine patients enrolled in the phase I showed dose-limiting toxicities at any level and thus, 52 patients were subsequently enrolled into a phase II, where Kypho-IORT was performed at various dose levels. The median pain score significantly dropped from 5 preoperatively to 2 at the first postoperative day (p<.001). Of 43 patients who reported a pre-interventional pain level of 3 or more, 30 (69.8%) reported a reduction of ≥3 points on the first postoperative day. A persistent pain reduction beyond the first postoperative day of ≥3 points was seen in 34 (79.1%) patients. The 3, 6, and 12 month L-PFS was excellent with 97.5%, 93.8%, and 93.8%. The 3, 6, and 12 months OS was 76.9%, 64.0%, and 48.4%. Conclusion Kyphoplasty and intraoperative radiotherapy is safe and immediately provided sustained pain relief with excellent local control rates in patients with painful vertebral metastases.